In this theory we consider right and left translations and odd functions.
In this section we consider translations. Translations are maps \(T: G\rightarrow G\) of the form \(T_g (a) = g\cdot a\) or \(T_g (a) = a\cdot g\). We also consider two-dimensional translations \(T_g : G\times G \rightarrow G\times G\), where \(T_g(a,b) = (a\cdot g, b\cdot g)\) or \(T_g(a,b) = (g\cdot a, g\cdot b)\).
For an element \(a\in G\) the right translation is defined a function (set of pairs) such that its value (the second element of a pair) is the value of the group operation on the first element of the pair and \(g\). This looks a bit strange in the raw set notation, when we write a function explicitely as a set of pairs and value of the group operation on the pair \(\langle a,b \rangle\) as \( P\langle a,b\rangle \) instead of the usual infix \(a\cdot b\) or \(a + b\).
definition
\( \text{RightTranslation}(G,P,g) \equiv \{\langle a,b\rangle \in G\times G.\ P\langle a,g\rangle = b\} \)
A similar definition of the left translation.
definition
\( \text{LeftTranslation}(G,P,g) \equiv \{\langle a,b\rangle \in G\times G.\ P\langle g,a\rangle = b\} \)
Translations map \(G\) into \(G\). Two dimensional translations map \(G\times G\) into itself.
lemma (in group0) group0_5_L1:
assumes A1: \( g\in G \)
shows \( \text{RightTranslation}(G,P,g) : G\rightarrow G \) and \( \text{LeftTranslation}(G,P,g) : G\rightarrow G \)proofThe values of the translations are what we expect.
lemma (in group0) group0_5_L2:
assumes \( g\in G \), \( a\in G \)
shows \( \text{RightTranslation}(G,P,g)(a) = a\cdot g \), \( \text{LeftTranslation}(G,P,g)(a) = g\cdot a \) using assms, group0_5_L1, RightTranslation_def, LeftTranslation_def, func1_1_L11BComposition of left translations is a left translation by the product.
lemma (in group0) group0_5_L4:
assumes A1: \( g\in G \), \( h\in G \), \( a\in G \) and A2: \( T_g = \text{LeftTranslation}(G,P,g) \), \( T_h = \text{LeftTranslation}(G,P,h) \)
shows \( T_g(T_h(a)) = g\cdot h\cdot a \), \( T_g(T_h(a)) = \text{LeftTranslation}(G,P,g\cdot h)(a) \)proofComposition of right translations is a right translation by the product.
lemma (in group0) group0_5_L5:
assumes A1: \( g\in G \), \( h\in G \), \( a\in G \) and A2: \( T_g = \text{RightTranslation}(G,P,g) \), \( T_h = \text{RightTranslation}(G,P,h) \)
shows \( T_g(T_h(a)) = a\cdot h\cdot g \), \( T_g(T_h(a)) = \text{RightTranslation}(G,P,h\cdot g)(a) \)proofPoint free version of group0_5_L4 and group0_5_L5.
lemma (in group0) trans_comp:
assumes \( g\in G \), \( h\in G \)
shows \( \text{RightTranslation}(G,P,g)\circ \text{RightTranslation}(G,P,h) = \text{RightTranslation}(G,P,h\cdot g) \), \( \text{LeftTranslation}(G,P,g)\circ \text{LeftTranslation}(G,P,h) = \text{LeftTranslation}(G,P,g\cdot h) \)proofThe image of a set under a composition of translations is the same as the image under translation by a product.
lemma (in group0) trans_comp_image:
assumes A1: \( g\in G \), \( h\in G \) and A2: \( T_g = \text{LeftTranslation}(G,P,g) \), \( T_h = \text{LeftTranslation}(G,P,h) \)
shows \( T_g(T_h(A)) = \text{LeftTranslation}(G,P,g\cdot h)(A) \)proofAnother form of the image of a set under a composition of translations
lemma (in group0) group0_5_L6:
assumes A1: \( g\in G \), \( h\in G \) and A2: \( A\subseteq G \) and A3: \( T_g = \text{RightTranslation}(G,P,g) \), \( T_h = \text{RightTranslation}(G,P,h) \)
shows \( T_g(T_h(A)) = \{a\cdot h\cdot g.\ a\in A\} \)proofThe translation by neutral element is the identity on group.
lemma (in group0) trans_neutral:
shows \( \text{RightTranslation}(G,P,1 ) = id(G) \) and \( \text{LeftTranslation}(G,P,1 ) = id(G) \)proofTranslation by neutral element does not move sets.
lemma (in group0) trans_neutral_image:
assumes \( V\subseteq G \)
shows \( \text{RightTranslation}(G,P,1 )(V) = V \) and \( \text{LeftTranslation}(G,P,1 )(V) = V \) using assms, trans_neutral, image_id_sameComposition of translations by an element and its inverse is identity.
lemma (in group0) trans_comp_id:
assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g)\circ \text{RightTranslation}(G,P,g^{-1}) = id(G) \) and \( \text{RightTranslation}(G,P,g^{-1})\circ \text{RightTranslation}(G,P,g) = id(G) \) and \( \text{LeftTranslation}(G,P,g)\circ \text{LeftTranslation}(G,P,g^{-1}) = id(G) \) and \( \text{LeftTranslation}(G,P,g^{-1})\circ \text{LeftTranslation}(G,P,g) = id(G) \) using assms, inverse_in_group, trans_comp, group0_2_L6, trans_neutralTranslations are bijective.
lemma (in group0) trans_bij:
assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g) \in \text{bij}(G,G) \) and \( \text{LeftTranslation}(G,P,g) \in \text{bij}(G,G) \)proofConverse of a translation is translation by the inverse.
lemma (in group0) trans_conv_inv:
assumes \( g\in G \)
shows \( converse( \text{RightTranslation}(G,P,g)) = \text{RightTranslation}(G,P,g^{-1}) \) and \( converse( \text{LeftTranslation}(G,P,g)) = \text{LeftTranslation}(G,P,g^{-1}) \) and \( \text{LeftTranslation}(G,P,g) = converse( \text{LeftTranslation}(G,P,g^{-1})) \) and \( \text{RightTranslation}(G,P,g) = converse( \text{RightTranslation}(G,P,g^{-1})) \)proofThe image of a set by translation is the same as the inverse image by by the inverse element translation.
lemma (in group0) trans_image_vimage:
assumes \( g\in G \)
shows \( \text{LeftTranslation}(G,P,g)(A) = \text{LeftTranslation}(G,P,g^{-1})^{-1}(A) \) and \( \text{RightTranslation}(G,P,g)(A) = \text{RightTranslation}(G,P,g^{-1})^{-1}(A) \) using assms, trans_conv_inv, vimage_converseAnother way of looking at translations is that they are sections of the group operation.
lemma (in group0) trans_eq_section:
assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g) = \text{Fix2ndVar}(P,g) \) and \( \text{LeftTranslation}(G,P,g) = \text{Fix1stVar}(P,g) \)proofA lemma demonstrating what is the left translation of a set
lemma (in group0) ltrans_image:
assumes A1: \( V\subseteq G \) and A2: \( x\in G \)
shows \( \text{LeftTranslation}(G,P,x)(V) = \{x\cdot v.\ v\in V\} \)proofA lemma demonstrating what is the right translation of a set
lemma (in group0) rtrans_image:
assumes A1: \( V\subseteq G \) and A2: \( x\in G \)
shows \( \text{RightTranslation}(G,P,x)(V) = \{v\cdot x.\ v\in V\} \)proofRight and left translations of a set are subsets of the group. Interestingly, we do not have to assume the set is a subset of the group.
lemma (in group0) lrtrans_in_group:
assumes \( x\in G \)
shows \( \text{LeftTranslation}(G,P,x)(V) \subseteq G \) and \( \text{RightTranslation}(G,P,x)(V) \subseteq G \)proofA technical lemma about solving equations with translations.
lemma (in group0) ltrans_inv_in:
assumes A1: \( V\subseteq G \) and A2: \( y\in G \) and A3: \( x \in \text{LeftTranslation}(G,P,y)( \text{GroupInv}(G,P)(V)) \)
shows \( y \in \text{LeftTranslation}(G,P,x)(V) \)proofWe can look at the result of interval arithmetic operation as union of left translated sets.
lemma (in group0) image_ltrans_union:
assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( (P \text{ lifted to subsets of } G)\langle A,B\rangle = (\bigcup a\in A.\ \text{LeftTranslation}(G,P,a)(B)) \)proofThe right translation version of image_ltrans_union The proof follows the same schema.
lemma (in group0) image_rtrans_union:
assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( (P \text{ lifted to subsets of } G)\langle A,B\rangle = (\bigcup b\in B.\ \text{RightTranslation}(G,P,b)(A)) \)proofIf the neutral element belongs to a set, then an element of group belongs the translation of that set.
lemma (in group0) neut_trans_elem:
assumes A1: \( A\subseteq G \), \( g\in G \) and A2: \( 1 \in A \)
shows \( g \in \text{LeftTranslation}(G,P,g)(A) \), \( g \in \text{RightTranslation}(G,P,g)(A) \)proofThe neutral element belongs to the translation of a set by the inverse of an element that belongs to it.
lemma (in group0) elem_trans_neut:
assumes A1: \( A\subseteq G \) and A2: \( g\in A \)
shows \( 1 \in \text{LeftTranslation}(G,P,g^{-1})(A) \), \( 1 \in \text{RightTranslation}(G,P,g^{-1})(A) \)proofThis section is about odd functions.
Odd functions are those that commute with the group inverse: \(f(a^{-1}) = (f(a))^{-1}.\)
definition
\( \text{IsOdd}(G,P,f) \equiv (\forall a\in G.\ f( \text{GroupInv}(G,P)(a)) = \text{GroupInv}(G,P)(f(a)) ) \)
Let's see the definition of an odd function in a more readable notation.
lemma (in group0) group0_6_L1:
shows \( \text{IsOdd}(G,P,p) \longleftrightarrow ( \forall a\in G.\ p(a^{-1}) = (p(a))^{-1} ) \) using IsOdd_defWe can express the definition of an odd function in two ways.
lemma (in group0) group0_6_L2:
assumes A1: \( p : G\rightarrow G \)
shows \( (\forall a\in G.\ p(a^{-1}) = (p(a))^{-1}) \longleftrightarrow (\forall a\in G.\ (p(a^{-1}))^{-1} = p(a)) \)proofThe section Binary operations in the func_ZF theory defines the notion of "lifting operation to subsets". In short, every binary operation \(f:X\times X \longrightarrow X \) on a set \(X\) defines an operation on the subsets of \(X\) defined by \(F(A,B) = \{ f\langle x,y \rangle | x\in A, y\in B\}\). In the group context using multiplicative notation we can write this as \(H\cdot K = \{ x\cdot y | x\in A, y\in B\}\). Similarly we can define \(H^{-1}=\{ x^{-1} | x\in H\}\). In this section we study properties of these derived operations and how they relate to the concept of subgroups.
The next locale extends the groups0 locale with notation related to interval arithmetics.
locale group4 = group0 +
defines \( A\cdot B \equiv (P \text{ lifted to subsets of } G)\langle A,B\rangle \)
defines \( A^{-1} \equiv \text{GroupInv}(G,P)(A) \)
The next lemma shows a somewhat more explicit way of defining the product of two subsets of a group.
lemma (in group4) interval_prod:
assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( A\cdot B = \{x\cdot y.\ \langle x,y\rangle \in A\times B\} \) using assms, group_oper_fun, lift_subsets_explainedProduct of elements of subsets of the group is in the set product of those subsets
lemma (in group4) interval_prod_el:
assumes \( A\subseteq G \), \( B\subseteq G \), \( x\in A \), \( y\in B \)
shows \( x\cdot y \in A\cdot B \) using assms, interval_prodAn alternative definition of a group inverse of a set.
lemma (in group4) interval_inv:
assumes \( A\subseteq G \)
shows \( A^{-1} = \{x^{-1}.\ x\in A\} \)proofGroup inverse of a set is a subset of the group. Interestingly we don't need to assume the set is a subset of the group.
lemma (in group4) interval_inv_cl:
shows \( A^{-1} \subseteq G \)proofThe product of two subsets of a group is a subset of the group.
lemma (in group4) interval_prod_closed:
assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( A\cdot B \subseteq G \)proofThe product of sets operation is associative.
lemma (in group4) interval_prod_assoc:
assumes \( A\subseteq G \), \( B\subseteq G \), \( C\subseteq G \)
shows \( A\cdot B\cdot C = A\cdot (B\cdot C) \)proofA simple rearrangement following from associativity of the product of sets operation.
lemma (in group4) interval_prod_rearr1:
assumes \( A\subseteq G \), \( B\subseteq G \), \( C\subseteq G \), \( D\subseteq G \)
shows \( A\cdot B\cdot (C\cdot D) = A\cdot (B\cdot C)\cdot D \)proofA subset \(A\) of the group is closed with respect to the group operation iff \(A\cdot A \subseteq A\).
lemma (in group4) subset_gr_op_cl:
assumes \( A\subseteq G \)
shows \( (A \text{ is closed under } P) \longleftrightarrow A\cdot A \subseteq A \)proofInverse and square of a subgroup is this subgroup.
lemma (in group4) subgroup_inv_sq:
assumes \( \text{IsAsubgroup}(H,P) \)
shows \( H^{-1} = H \) and \( H\cdot H = H \)proofInverse of a product two sets is a product of inverses with the reversed order.
lemma (in group4) interval_prod_inv:
assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( (A\cdot B)^{-1} = \{(x\cdot y)^{-1}.\ \langle x,y\rangle \in A\times B\} \), \( (A\cdot B)^{-1} = \{y^{-1}\cdot x^{-1}.\ \langle x,y\rangle \in A\times B\} \), \( (A\cdot B)^{-1} = (B^{-1})\cdot (A^{-1}) \)proofIf \(H,K\) are subgroups then \(H\cdot K\) is a subgroup iff \(H\cdot K = K\cdot H\).
theorem (in group4) prod_subgr_subgr:
assumes \( \text{IsAsubgroup}(H,P) \) and \( \text{IsAsubgroup}(K,P) \)
shows \( \text{IsAsubgroup}(H\cdot K,P) \longleftrightarrow H\cdot K = K\cdot H \)proofassumes \( \forall x\in X.\ b(x) \in Y \)
shows \( \{\langle x,y\rangle \in X\times Y.\ b(x) = y\} : X\rightarrow Y \)assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g) : G\rightarrow G \) and \( \text{LeftTranslation}(G,P,g) : G\rightarrow G \)assumes \( f:X\rightarrow Y \), \( x\in X \) and \( f = \{\langle x,y\rangle \in X\times Y.\ b(x) = y\} \)
shows \( f(x) = b(x) \)assumes \( g\in G \), \( a\in G \)
shows \( \text{RightTranslation}(G,P,g)(a) = a\cdot g \), \( \text{LeftTranslation}(G,P,g)(a) = g\cdot a \)assumes \( a\in G \), \( b\in G \), \( c\in G \)
shows \( a\cdot (b\cdot c) = a\cdot b\cdot c \)assumes \( a\in G \), \( b\in G \)
shows \( a\cdot b \in G \)assumes \( g\in G \), \( h\in G \), \( a\in G \) and \( T_g = \text{RightTranslation}(G,P,g) \), \( T_h = \text{RightTranslation}(G,P,h) \)
shows \( T_g(T_h(a)) = a\cdot h\cdot g \), \( T_g(T_h(a)) = \text{RightTranslation}(G,P,h\cdot g)(a) \)assumes \( f: X\rightarrow Y \), \( g: X\rightarrow Z \) and \( \forall x\in X.\ f(x) = g(x) \)
shows \( f = g \)assumes \( g\in G \), \( h\in G \), \( a\in G \) and \( T_g = \text{LeftTranslation}(G,P,g) \), \( T_h = \text{LeftTranslation}(G,P,h) \)
shows \( T_g(T_h(a)) = g\cdot h\cdot a \), \( T_g(T_h(a)) = \text{LeftTranslation}(G,P,g\cdot h)(a) \)assumes \( g\in G \), \( h\in G \)
shows \( \text{RightTranslation}(G,P,g)\circ \text{RightTranslation}(G,P,h) = \text{RightTranslation}(G,P,h\cdot g) \), \( \text{LeftTranslation}(G,P,g)\circ \text{LeftTranslation}(G,P,h) = \text{LeftTranslation}(G,P,g\cdot h) \)assumes \( f:X\rightarrow Y \) and \( g:Y\rightarrow Z \) and \( A\subseteq X \)
shows \( g(f(A)) = \{g(f(x)).\ x\in A\} \), \( g(f(A)) = (g\circ f)(A) \)assumes \( f:X\rightarrow Y \) and \( \forall x\in X.\ f(x)=x \)
shows \( f = id(X) \)assumes \( A\subseteq X \)
shows \( id(X)(A) = A \)assumes \( x\in G \)
shows \( x^{-1}\in G \)assumes \( x\in G \)
shows \( x\cdot x^{-1} = 1 \wedge x^{-1}\cdot x = 1 \)assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g)\circ \text{RightTranslation}(G,P,g^{-1}) = id(G) \) and \( \text{RightTranslation}(G,P,g^{-1})\circ \text{RightTranslation}(G,P,g) = id(G) \) and \( \text{LeftTranslation}(G,P,g)\circ \text{LeftTranslation}(G,P,g^{-1}) = id(G) \) and \( \text{LeftTranslation}(G,P,g^{-1})\circ \text{LeftTranslation}(G,P,g) = id(G) \)assumes \( g\in G \)
shows \( \text{RightTranslation}(G,P,g) \in \text{bij}(G,G) \) and \( \text{LeftTranslation}(G,P,g) \in \text{bij}(G,G) \)assumes \( a \in \text{bij}(A,B) \), \( b \in \text{bij}(B,A) \) and \( b\circ a = id(A) \)
shows \( a = converse(b) \) and \( b = converse(a) \)assumes \( g\in G \)
shows \( converse( \text{RightTranslation}(G,P,g)) = \text{RightTranslation}(G,P,g^{-1}) \) and \( converse( \text{LeftTranslation}(G,P,g)) = \text{LeftTranslation}(G,P,g^{-1}) \) and \( \text{LeftTranslation}(G,P,g) = converse( \text{LeftTranslation}(G,P,g^{-1})) \) and \( \text{RightTranslation}(G,P,g) = converse( \text{RightTranslation}(G,P,g^{-1})) \)assumes \( f : X\times Y \rightarrow Z \) and \( y\in Y \)
shows \( \text{Fix2ndVar}(f,y) : X \rightarrow Z \)assumes \( f : X\times Y \rightarrow Z \) and \( x\in X \), \( y\in Y \)
shows \( \text{Fix1stVar}(f,x)(y) = f\langle x,y\rangle \), \( \text{Fix2ndVar}(f,y)(x) = f\langle x,y\rangle \)assumes \( f : X\times Y \rightarrow Z \) and \( x\in X \)
shows \( \text{Fix1stVar}(f,x) : Y \rightarrow Z \)assumes \( f:X\rightarrow Y \) and \( A\subseteq X \)
shows \( f(A) = \{f(x).\ x \in A\} \)assumes \( f:X\rightarrow Y \)
shows \( f(B) \subseteq \text{range}(f) \) and \( f(B) \subseteq Y \)assumes \( f:X\rightarrow Y \)
shows \( f(B) \subseteq \text{range}(f) \) and \( f(B) \subseteq Y \)assumes \( \text{IsAgroup}(G,f) \)
shows \( \text{GroupInv}(G,f) : G\rightarrow G \)assumes \( V\subseteq G \) and \( x\in G \)
shows \( \text{LeftTranslation}(G,P,x)(V) = \{x\cdot v.\ v\in V\} \)assumes \( a\in G \), \( b\in G \)
shows \( a\cdot b^{-1}\cdot b = a \), \( a\cdot b\cdot b^{-1} = a \), \( a^{-1}\cdot (a\cdot b) = b \), \( a\cdot (a^{-1}\cdot b) = b \)assumes \( f : X\times X \rightarrow Y \) and \( A \subseteq X \), \( B \subseteq X \) and \( F = f \text{ lifted to subsets of } X \)
shows \( F\langle A,B\rangle \subseteq Y \) and \( F\langle A,B\rangle = f(A\times B) \), \( F\langle A,B\rangle = \{f(p).\ p \in A\times B\} \), \( F\langle A,B\rangle = \{f\langle x,y\rangle .\ \langle x,y\rangle \in A\times B\} \)assumes \( V\subseteq G \) and \( x\in G \)
shows \( \text{RightTranslation}(G,P,x)(V) = \{v\cdot x.\ v\in V\} \)assumes \( a\in G \)
shows \( a = (a^{-1})^{-1} \)assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( A\cdot B = \{x\cdot y.\ \langle x,y\rangle \in A\times B\} \)assumes \( f \text{ is associative on } X \) and \( F = f \text{ lifted to subsets of } X \)
shows \( F \text{ is associative on } Pow(X) \)assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( A\cdot B \subseteq G \)assumes \( A\subseteq G \), \( B\subseteq G \), \( C\subseteq G \)
shows \( A\cdot B\cdot C = A\cdot (B\cdot C) \)assumes \( \text{IsAsubgroup}(H,P) \)
shows \( H \subseteq G \)assumes \( A\subseteq G \)
shows \( A^{-1} = \{x^{-1}.\ x\in A\} \)assumes \( \text{IsAsubgroup}(H,P) \) and \( h\in H \)
shows \( h^{-1}\in H \)assumes \( \text{IsAsubgroup}(H,P) \) and \( a\in H \), \( b\in H \)
shows \( a\cdot b \in H \)assumes \( A\subseteq G \)
shows \( (A \text{ is closed under } P) \longleftrightarrow A\cdot A \subseteq A \)assumes \( \text{IsAsubgroup}(H,P) \)
shows \( 1 \in H \)assumes \( a\in G \) and \( b\in G \)
shows \( b^{-1}\cdot a^{-1} = (a\cdot b)^{-1} \)assumes \( \text{IsAsubgroup}(H,P) \)
shows \( H^{-1} = H \) and \( H\cdot H = H \)assumes \( A\subseteq G \), \( B\subseteq G \)
shows \( (A\cdot B)^{-1} = \{(x\cdot y)^{-1}.\ \langle x,y\rangle \in A\times B\} \), \( (A\cdot B)^{-1} = \{y^{-1}\cdot x^{-1}.\ \langle x,y\rangle \in A\times B\} \), \( (A\cdot B)^{-1} = (B^{-1})\cdot (A^{-1}) \)assumes \( A\subseteq G \), \( B\subseteq G \), \( C\subseteq G \), \( D\subseteq G \)
shows \( A\cdot B\cdot (C\cdot D) = A\cdot (B\cdot C)\cdot D \)assumes \( \text{IsAsubgroup}(H,P) \)
shows \( H^{-1} = H \) and \( H\cdot H = H \)assumes \( H\neq 0 \) and \( H\subseteq G \) and \( H \text{ is closed under } P \) and \( \forall x\in H.\ x^{-1} \in H \)
shows \( \text{IsAsubgroup}(H,P) \)